(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:Search goal:1- The effect of a cognitive behavioral counseling program on developing the skill of effective communication among female students of the departments of psychological counseling and educational guidance in the faculties of basic education.In order to verify this goal, the following zero hypotheses were derived:- The first hypothesis: (There are no statistically significant differences at the level of significance (0.05) between the mean scores of the experimental group students in the pre and post tests on the effective communication skill scale after applying the counseling program)- The second hypothesis: (There are no statistically significant differences at the level of significance (0.05) between the mean scores of the students of the experimental group and the average ranks of the scores of the students of the control group on the distance communication skill scale after applying the counseling program).For the purpose of testing the hypotheses of the research, the researchers chose the experimental design (the design of the experimental group and the control group with two pre and post tests), as the research sample consisted of (24) female students from the psychological counseling and educational guidance departments, who had obtained lower scores than the hypothetical average in the effective communication skill scale. The counseling program consisted of (12) counseling sessions, and the topics of the sessions were chosen in the light of the paragraphs of the effective communication skill scale. The duration of each session was (45) minutes, and each session had its own goals, behavioral objectives, and counseling techniques according to the cognitive-behavioral counseling theory of (Aaron Beck), with two sessions. per week, and the research reached the following results:1. There are statistically significant differences between the mean scores of the experimental group members in developing the skill of effective communication among female students of the departments of psychological counseling and educational guidance in the pre and post tests on the effective communication skill scale in favor of the post test.2. There are statistically significant differences between the mean scores of the experimental group and the control group on the effective communication skill scale in the post-test after applying the counseling program in favor of the experimental group.It turned out that the level of the size of the effect left by the counseling program in developing the skill of effective communication between the experimental and control groups in the post-test was large and amounted to (0.69) according to the ETA equation, and also the size of the effect was large between the pre-test and the post-test of the experimental group, which amounted to (4,354). ) According to Cohen’s equation in light of the levels identified by Cohen in judging the level of impact.As a complement to the current research, the two researchers presented a number of recommendations and proposals.• Keywords: impact, counseling program